IMPLEMENTASI PROGRAM CSR PERUSAHAAN DALAM PEMBERDAYAAN PEREKONOMIAN MASYARAKAT PEDESAAN DI MASA PANDEMI COVID-19 BERDASARKAN PERATURAN DAERAH PROVINSI RIAU NOMOR 6 TAHUN 2012 - Andrew Shandy Utama (Universitas Islam Negeri sultan syarif kasim Riau, 2022)
This research aims to explain the implementation of the company's CSR program in empowering the economy of rural communities during the Covid-19 pandemic based on Riau Provincial Regulation Number 6 of 2012. The method used in this research is socio-legal research. The results of this research explain that the Covid-19 Pandemic that hit Riau Province had an impact on the economy of the community, including the people of Palas Village. Apart from expecting financial assistance from the government, one of the opportunities that the Palas Village community can take advantage of to develop the village economy is to take advantage of the CSR programs of companies operating in Pelalawan Regency. Companies that carry out their business activities in the field of natural resources and / or fields related to natural resources are required to carry out CSR. Based on Article 32 of Riau Provincial Regulation Number 6 of 2012, it is stated that companies that don’t implement CSR are subject to administrative sanctions in the form of written warnings and restrictions on business activities, freezing of business activities, and revocation of business activities.